Systematic analysis and prediction of the burden of lower respiratory tract infections attribute to non-optimal temperature, 1990–2019 - Shi, Yu; Zhang, Liping; Wu, Di; Yilihamu, Yilipa; Wang, Lei (Frontiers in Public Health, 2024)
Background Lower respiratory infections (LRIs) remain one of the most deadly infectious diseases in the world, and non-optimal temperature is a risk factor for LRIs. The aim of this study was to analyze the global burden of LRI attribute to non-optimal temperature and its trends from 1990 to 2019, and to project long-term trends. Methods Excerpts from the release of the 2019 Global Burden of Disease (GBD) study, which analyses the burden of lower respiratory infections due to non-optimal temperatures from 1990 to 2019 using data on deaths and disability adjusted life years (DALYs); explores differences across regions, populations and seasons, and projects future trends in burden. Results Between 1990 and 2019, there is a significant downward trend in the global burden of deaths and DALYs, but it remains high in infants and young children, the older adult, African countries and LOW SDI regions. Differences in geographical risk factors and economic levels lead to heterogeneous disease burdens across regions. In 2019, low SDI regions will have the highest burden, but high SDI regions will have the highest number of deaths. In addition, increasing SDI values were associated with decreasing trends in age-standardized mortality rates and disability-adjusted life years. BAPC model projections suggest a downward trend in the future burden of death and DALYs from the disease, but the improvement in the burden of death for women was not significant. Conclusion Our study comprehensively elucidates the distribution and dynamic trends in the burden of lower respiratory tract infections due to non-optimal temperatures from 1990 to 2019 along multiple dimensions. The burden of deaths and DALYs showed an overall decreasing trend, but the improvement was uneven in different regions. In addition, the results suggest that efforts should be made to reduce lower respiratory health losses in infants, young children, and older adult populations. Effective public health policies and interventions to reduce the burden of lower respiratory tract infections should be sustained globally.